Pengaruh Partisipasi Anggaran, Kejelasan Sasaran Anggaran dan Kohesivitas Kelompok terhadap Senjangan Anggaran - Evitania Precilia, Ni Putu; Sri Harta Mimba, Ni Putu (E-Jurnal Akuntansi, 2020)
The purpose of this study was to examine the effect of budget participation, clarity of budget targets and group cohesiveness on budgetary slack at the Mangusada Regional Hospital in Badung Regency. A total of 36 people were selected as respondents. The sampling method in this study is purposive sampling and the data analysis technique of this study uses multiple linear regression analysis. The results of this study indicate that budgetary participation and group cohesiveness have a positive effect on budgetary slack, while the clarity of budget targets has a negative effect on budgetary slack in the Mangusada Regional Hospital in Badung Regency. Keywords: Budget Participation; Clarity of Budget Goals; Group Cohesiveness; Budgetary Slack.